Soil phosphorus mobilization as affected by long-term organic fertilization in a tropical Regosol - Kalline De Almeida Alves Carneiro; Tancredo Augusto Feitosa De Souza; Gislaine Dos Santos Nascimento; Vânia Da Silva Fraga; Bruno de Oliveira Dias (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Phosphorus mobilization (PM) in tropical Regosols may be harmful to the environment and water quality. It is expected that high contents of soluble phosphorus in sandy soils may promote the P leaching through the transport of the available phosphorus from the soil surface to deeper layers. This study aimed to evaluate the PM in a tropical Regosol by using soil columns (10 cm depth) during steady saturated water flow and PM was correlated with Fe and Al oxides. Method: Soil samples were collected in four sites characterized as smallholder farming systems that shared the same land uses and soil type with each other. P content was estimated by using water, Melich-1, and resin extraction protocols. We estimated the contents of Fe and Al oxides with high and low crystallinity. The miscible displacement technique was used to simulate P leaching in soil columns, and the leached P was quantified by colorimetry. Results: Soil P loss showed a significant coefficient of determination (r2 > 0.80) with P content. We found the highest values of Fe oxalate (0.30 mg/g), and Al oxalate (0.53 mg/g) in the long-term organic fertilization, while the highest values of Fe dithionite and Al dithionite were found with the non-fertilization system. Conclusion: The highest soil pH (8.01), soil P content by different extractors (P mehlich-1, P water, and P resin were 54.45, 14.36, and, 38.70 mg/kg, respectively), and soil P loss (128.83 mg/kg) were observed with the long-term non-fertilization system. Highlights: